2010
DOI: 10.1002/biot.201000245
|View full text |Cite
|
Sign up to set email alerts
|

Chitin deacetylase product inhibition

Abstract: Chitin deacetylase is the only known enzyme catalyzing the hydrolysis of the acetamino linkage in the N-acetylglucosamine units of chitin and chitosan. This reaction can play an important role in enzymatic production of chitosan from chitin, or in enzymatic modification of chitosan, which has applications in medicine, pharmacy or plant protection. It was previously shown that acetic acid, a product of the deacetylation process, may act as an inhibitor of chitin deacetylase. Here we show the mechanism of inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The plates were left for 30 min at room temperature to allow compound diffusion and then were incubated at 30°C for 36 h. Inhibition zone diameters were measured in triplicate in millimeters. Values are presented as means ± SD [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…The plates were left for 30 min at room temperature to allow compound diffusion and then were incubated at 30°C for 36 h. Inhibition zone diameters were measured in triplicate in millimeters. Values are presented as means ± SD [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…The AcOH formed during the deacetylation process may act as a competitive inhibitor of CDA. 44) For the enzyme purified from Mucor rouxii ATC C 24905, it was shown that AcOH at a concentration of 250 mM decreased the enzyme activity to 10% of the initial value. However, the influence of AcOH on CDA from Colletotrichum lindemuthianum ATC C 56676 was less significant.…”
Section: Cda Inhibitorsmentioning
confidence: 99%
“…Among the numerous studies on chitin deacetylase, some researchers have found that in 3.0 mol/L sodium acetate, ClCDA can participate in the reverse hydrolysis reaction, acetylate the free amino sugar residues into N-acetylated form, and some studies have confirmed that acetate plays a competitive inhibitory role in this process. This makes it possible to control plant pathogens by inhibiting chitin deacetylase [13][14][15].…”
Section: Introductionmentioning
confidence: 99%